2012
DOI: 10.1039/c2cc33090c
|View full text |Cite
|
Sign up to set email alerts
|

Controlled synthesis and alkaline earth ion binding of switchable formamidoxime-based crown ether analogs

Abstract: The partial positive charge of amide protons is used to promote macrocyclization and form crown-ether analogs. Their deprotonation generates very selective pH-switchable alkaline earth ion receptors only in the presence of an appropriate substrate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…Every independent molecule contains two symmetrical N-ethyl(pyridine-2-carboxiamide) moieties linked by a phenylamino bridge. It is noteworthy that the C═O bonds are oriented trans to the pyridine nitrogen atom, which are in accord with those reported for previous structures (Munro et al, 2010;Yan et al, 2012) [symmetry code: (iv) x+1/2, -y+1/2, z+1/2; (v) x-1/2, -y+1/2, z-1/2] (Table 1).…”
Section: Data Collectionsupporting
confidence: 90%
See 1 more Smart Citation
“…Every independent molecule contains two symmetrical N-ethyl(pyridine-2-carboxiamide) moieties linked by a phenylamino bridge. It is noteworthy that the C═O bonds are oriented trans to the pyridine nitrogen atom, which are in accord with those reported for previous structures (Munro et al, 2010;Yan et al, 2012) [symmetry code: (iv) x+1/2, -y+1/2, z+1/2; (v) x-1/2, -y+1/2, z-1/2] (Table 1).…”
Section: Data Collectionsupporting
confidence: 90%
“…For the synthesis, see: Jain et al (2004); Lee et al (2006); Barnes et al (1978). For related structures, see: Adolph et al (2012); Munro & Wilson (2010); Yan et al (2012). Cu K radiation = 0.70 mm À1 T = 100 K 0.12 Â 0.08 Â 0.07 mm…”
Section: Related Literaturementioning
confidence: 99%
“…Small model systems with intramolecular and/or intermolecular hydrogen bonded amide groups are often employed to study these interactions in solution and in the solid state [ 4 ]. Aminobenzamides, for example, are commonly used as hydrogen-bond donors to form intramolecular hydrogen bonds with other O - or N -groups as hydrogen-bond acceptors [ 5 , 6 ]. The amides also work as dual hydrogen-bond donors and acceptors to form intramolecular hydrogen bonds between the adjacent amide-amide groups to construct linear sheets and helical conformations [ 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…2 Conjugation by opening of the anhydride could form two isomers but NMR studies showed only a single isomer to be formed. L 37 has been conjugated to trastuzumab at 25 1C and radiolabelled with 111 In for tumour targeted SPECT imaging. 3 A strain promoted catalyst free click reaction has been tested for peptide conjugation reaction of chelators for radioisotope complexation to avoid the problems of copper catalyst contamination.…”
Section: Targeted Radiopharmaceuticalsmentioning
confidence: 99%
“…A chelator combining amide and oxime groups L 68 selectively complexes alkaline earth ions such as calcium(II) with a pH dependence linked to protonation and cavity H-bonding motifs. 111…”
Section: Mixed Donor Macrocyclesmentioning
confidence: 99%